STATUS MUTU KUALITAS AIR WADUK TAKISUNG DESA BANUA TENGAH KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Abdur Rahman; Sri Nurhayati; Mahdah Mahdiah; M. Ryan Hidayat (Universitas Lambung Mangkurat, 2018)
The results of this research aim to determine the status of water quality using the Storet method. From the results of the study, the results of the measurement of the quality of water in the Takisung 1 Reservoir for DO parameters were 7.0 Mg/l, a temperature of 31.9oC, a pH of 5.0, phosphate of 0.27 Mg/l, and Nitrate of 0.2 Mg/l. Measurement of the quality of water in Takisung 2 Reservoir for DO parameters 7.7 Mg/l. The temperature is 30.8 oC, pH is 5.5, Phosphate is 0.04 Mg/l and Nitrate is 0.4 Mg/l. Based on the calculation of the status of the water quality of the Storet method, the Takisung 1 and 2 reservoirs are classified as lightly polluted. Based on the carrying capacity analysis of biota using the calculation of the analysis of phytoplankton and zooplankton, the abundance of phytoplankton in the Takisung 1 reservoir was 520 cells/liter, included in the medium fertility category. Diversity index is equal to 0.3010 (unstable and is in a heavily polluted condition). In the Takisung 2 Reservoir, the abundance value of 250 cells / l was obtained (medium fertility category). Diversity index of 0.6005 (category is not stable and is in a heavily polluted condition). The abundance of zooplankton in the Takisung 1 reservoir is 530 individuals / l, included in the medium fertility category. The diversity index is 0.5997 (the category is unstable and is in a heavily polluted condition). The abundance of zooplankton in the Takisung 2 reservoir is 560 individuals / including in the medium fertility category. The diversity index of 0.2089 is included in the category of being unstable and in a heavily polluted condition.